2016
DOI: 10.1002/bjs.10060
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial comparing long-term quality of life for Billroth IversusRoux-en-Y reconstruction after distal gastrectomy for gastric cancer

Abstract: NCT01065688 (http://www.clinicaltrials.gov).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
51
3
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 41 publications
2
51
3
2
Order By: Relevance
“…Nakamura et al . also found that symptom scales at 12 months were not significantly different, but were significantly better in the B-I group at 36 months after gastrectomy 34 . These were different from the previous studies indicating that the postoperative 6 months was a cut-point of QoL 35 , 36 .…”
Section: Discussionmentioning
confidence: 80%
“…Nakamura et al . also found that symptom scales at 12 months were not significantly different, but were significantly better in the B-I group at 36 months after gastrectomy 34 . These were different from the previous studies indicating that the postoperative 6 months was a cut-point of QoL 35 , 36 .…”
Section: Discussionmentioning
confidence: 80%
“… 20 21 Although this surgery takes more time to perform, it is expected to become more commonly performed based on its clear advantages; however, debate remains, and further studies are required. 22 …”
Section: Discussionmentioning
confidence: 99%
“…17 Cai et al reviewed the reconstruction method after distal gastrectomy, and LA classification was used in 3 of 8 papers, and 4 of 8 papers reported results according to RGB classification. [23][24][25][26][27][28] Again, only one in eight papers reported results for all three: LA classification, RGB classification, and ref lux symptom. 26 The limitations of this study are that it is a retrospective observational study, that only three surgeons in a single center participated, and there was a small sample size as an observational study.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28] Again, only one in eight papers reported results for all three: LA classification, RGB classification, and ref lux symptom. 26 The limitations of this study are that it is a retrospective observational study, that only three surgeons in a single center participated, and there was a small sample size as an observational study. Additionally, we did not find strong evidence to prove safety and effectiveness of the new surgical technique.…”
Section: Discussionmentioning
confidence: 99%